2018
DOI: 10.1021/jacs.8b09311
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence Enhancement of a Microbial Rhodopsin via Electronic Reprogramming

Abstract: The engineering of microbial rhodopsins with enhanced fluorescence is of great importance in the expanding field of optogenetics. Here we report the discovery of two mutants (W76S/Y179F and L83Q) of a sensory rhodopsin from the cyanobacterium Anabaena PCC7120 with opposite fluorescence behavior. In fact, while W76S/Y179F displays, with respect to the wild-type protein, a nearly tenfold increase in red-light emission, the second is not emissive. Thus, the W76S/ Y179F, L83Q pair offers an unprecedented opportuni… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
66
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 42 publications
(73 citation statements)
references
References 51 publications
(92 reference statements)
5
66
2
Order By: Relevance
“…As observed in Figure 5A, the general trend for wild type and Rh mutants models is qualitatively reproduced, mostly displaying blue-shifted absorption similar to the results of the original ARM. 20,52,54,55 Actually, as can be seen in Figure 5B, 30 out of the 39 studied rhodopsins (77%) exhibit blue-shifted errors lower than 3 kcal mol -1 , 6 (15%) higher than 5 kcal mol -1 , and only 3 (8%) present red-shifted values of just few (0.5-1.6) kcal mol -1 . More specifically, among the m-set, BPR and ChR C1C2…”
Section: A-arm Defaultmentioning
confidence: 74%
See 2 more Smart Citations
“…As observed in Figure 5A, the general trend for wild type and Rh mutants models is qualitatively reproduced, mostly displaying blue-shifted absorption similar to the results of the original ARM. 20,52,54,55 Actually, as can be seen in Figure 5B, 30 out of the 39 studied rhodopsins (77%) exhibit blue-shifted errors lower than 3 kcal mol -1 , 6 (15%) higher than 5 kcal mol -1 , and only 3 (8%) present red-shifted values of just few (0.5-1.6) kcal mol -1 . More specifically, among the m-set, BPR and ChR C1C2…”
Section: A-arm Defaultmentioning
confidence: 74%
“…The current version of ARM has been tested for the prediction of trends in λ max a of a limited set of wild type and mutant vertebrate, invertebrate, and microbial rhodopsins, 10,20,52,54,55 showing good agreement with experimental data. The required input includes (A) an X-ray crystallographic structure or comparative model of the protein in PDB (Protein Data Bank) format, 56,57 (B) a list of residues forming the chromophore cavity, (C) the protonation states of ionizable side chains, and (D) the position of extracellular (OS) and intracellular (IS) counterions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thee xcited-state PES relevant to the photoisomerization process of various rhodopsins has been extensively discussed theoretically and experimentally. [7,31,36,50,[63][64][65][66][67][68][69] In particular, several recent quantum mechanics/molecular mechanics (QM/MM) calculations provided at heoretical view for the S 1 PES based on the mixing of the S 1 and S 2 states. [31,65,66,69] In this view,t he S 1 state has the polar 1B u electronic character that facilitates ultrafast isomerization due to the energetically down-hill nature along the isomerization coordinate,whereas the higher S 2 state has the nonpolar 2A g electronic character that prohibits the isomerization due to its bound-state nature.…”
Section: Methodsmentioning
confidence: 99%
“…[25] As more rhodopsins were discovered, aw ider variety of excited-state relaxation dynamics were observed. Fore xample,p roteorhodopsin (PR), [13,[26][27][28][29] Anabaena sensory rhodopsin [16,30,31] and KR2 [18] exhibit complicated excited-state decays that contain several fast (< 1ps) and slow (> 1ps) decay components.Sofar, this wide variety of the multi-phasic excited-state relaxation dynamics observed for different rhodopsins has been mainly explained with the branching of the relaxation pathways on the S 1 Recently,our group studied the primary photoreaction of novel sodium (Na + )-pumping rhodopsin KR2 using femtosecond time-resolved absorption (TA) spectroscopy. [38] It was found that the excited state of KR2 exhibits am ulti-phasic decay that consists of afast (< 1ps) decay and long-lived slow (> 1ps) decays.I nterestingly,t heir relative amplitude drastically changes around the pH corresponding to the pK a of Asp116, the counterion of the PRSB chromophore.T his result indicated that the multi-phasic excited-state decay in KR2 is attributable to the structural heterogeneity in the ground state,that is,the acid-base equilibrium of counterion, Asp116.…”
Section: Introductionmentioning
confidence: 99%